EFEKTIVITAS PEMBELAJARAN BERBASIS LEARNING MANAGEMENT SYSTEM TERHADAP HASIL BELAJAR PENDIDIKAN ISLAM - M. Zamzam; Deni Putra; Akwam (Jurnal Dinamika Pendidikan Islam, 2026)
The development of digital technology has driven the transformation from conventional learning to Learning Management System (LMS)-based learning in Islamic educational institutions. Purpose: This study aims to analyze the effectiveness of LMS-based learning on Islamic Education learning outcomes at the secondary education level. Method: The study employed a quasi-experimental approach with a pretest-posttest control group design, involving 60 students divided into experimental and control groups. Data collection instruments included learning outcome tests, motivation questionnaires, and observation. Results: Findings show a significant difference in learning outcomes between the experimental group (mean = 82.4) and the control group (mean = 71.3) with a sig. value of 0.001 < 0.05. Conclusion: LMS-based learning is proven more effective in improving Islamic Education learning outcomes compared to conventional learning, with a 34.5% increase in learning motivation